SEISMIC STRATIGRAPHIC AND STRUCTURAL CHARACTERIZATION OF XY-1 (TOMBOY) FIELD, OFFSHORE WESTERN NIGER DELTA, NIGERIA (FULafia Journal of Science and Technology, 2018)
The focal aim of the study is to map the structures in the study area using seismic characterization methodology. Key stratal terminations such as onlaps, toplaps and erosional unconformities (or truncations) were recognized. Nine surface boundaries, namely: four maximum flooding surfaces and five sequence boundaries were detected as peaks and troughs of the seismic onsets, respectively. The maximum flooding surfaces and the sequence boundaries depths were converted to time in milliseconds using check shot data. The converted time represents two-way travel time. Accordingly, the wireline logs were effectively tied to the seismic lines for better stratigraphic interpretation. The structural style of the field is characterized by two systems of antithetic and growth faults. On the seismic lines, shale structures were recognized as zones of chaotic or transparent seismic reflections